Anti‐corrosion property of superhydrophobic copper mesh with one‐step self‐assembled perfluorothiolate monolayers. (15th July 2022) - Feng, Jiekai; Chen, Faze; Chao, Jiaqi; Cai, Zexin; Liu, Teng; Zhang, Du; Tian, Yanling
Abstract : Copper mesh (CM) is one of the most commonly used engineering materials due to its remarkable mechanical and electromagnetic properties. However, CMs are generally susceptible to chemical corrosion in harsh environments, which greatly limits their long‐term usage. In this paper, we come up with a one‐step perfluorodecanethiol self‐assembly means to manufacture superhydrophobic CM with significantly improved anti‐corrosion property. The self‐assembly reaction between copper and 1 H, 1 H, 2 H, 2 H ‐perfluorodecanethiol created nanoscale rough structures and lowered the surface energy of the CM surface, which was account for the excellent repellence towards various aqueous solutions. The electrochemical tests demonstrated that, compared with original CM, the i corr value of the self‐assembled monolayers (SAMs) functionalized CM decreases about one order of magnitude, whereas the corrosion protection efficiency of the treated CM in NaCl, NaOH, and HCl aqueous solutions were all obviously increased. Therefore, the proposed simple method could be an alternative candidate for the creation of functional CM with anti‐corrosion properties that could be used under complex conditions.